Fungi from Admiralty Bay (King George Island, Antarctica) Soils and Marine Sediments - Wentzel, Lia Costa Pinto [UNESP]; Inforsato, Fábio José [UNESP]; Montoya, Quimi Vidaurre [UNESP]; Rossin, Bruna Gomes [UNESP]; Nascimento, Nadia Regina [UNESP]; Rodrigues, André [UNESP]; Sette, Lara Durães [UNESP] (Springer Nature, 2018)
Extreme environments such as the Antarctic can lead to the discovery of new microbial taxa, as well as to new microbial-derived natural products. Considering that little is known yet about the diversity and the genetic resources present in these habitats, the main objective of this study was to evaluate the fungal communities from extreme environments collected at Aldmiralty Bay (Antarctica). A total of 891 and 226 isolates was obtained from soil and marine sediment samples, respectively. The most abundant isolates from soil samples were representatives of the genera Leucosporidium, Pseudogymnoascus, and a non-identified Ascomycota NIA6. Metschnikowia sp. was the most abundant taxon from marine samples, followed by isolates from the genera Penicillium and Pseudogymnoascus. Many of the genera were exclusive in marine sediment or terrestrial samples. However, representatives of eight genera were found in both types of samples. Data from non-metric multidimensional scaling showed that each sampling site is unique in their physical-chemical composition and fungal community. Biotechnological potential in relation to enzymatic production at low/moderate temperatures was also investigated. Ligninolytic enzymes were produced by few isolates from root-associated soil. Among the fungi isolated from marine sediments, 16 yeasts and nine fungi showed lipase activity and three yeasts and six filamentous fungi protease activity. The present study permitted increasing our knowledge on the diversity of fungi that inhabit the Antarctic, finding genera that have never been reported in this environment before and discovering putative new species of fungi.
Keywords: Cold-adapted enzymes; Extremophiles; Fungal diversity; Marine mycology; Maritime Antarctica